Sustainability in hospitality - Wagner, Johanna (Henry Stewart Talks, 2024)
Planetary boundaries, Social and environmental issues, Relevant externalities, Hotel lifecycle, Traditional hotel business model, Sustainable hotel business model, Iberostar Dominican Republic example, Six Senses Maldives example